2021
DOI: 10.3390/nu13114112
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Crohn’s Disease Exclusion Diet for Induction of Remission in Crohn’s Disease Adult Patients

Abstract: Exclusive enteral nutrition (EEN) is a first-line treatment in active, mild to moderate Crohn’s disease (CD) in children. The Crohn’s disease exclusion diet (CDED), which avoids products known to have a pro-inflammatory effect on the intestinal mucosa, presents similar effectiveness to EEN for inducing remission in the paediatric population. The aim of the study was to evaluate the effectiveness of the CDED in inducing remission in adult patients. Between March 2020 and May 2021, 32 patients in a gastroenterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 18 publications
1
59
0
1
Order By: Relevance
“…In the patients under analysis, a 12-week treatment with CDED + PEN resulted in normalization of fecal calprotectin level in 35%, while 33% achieved such an effect in combination with normal CRP and PCDAI scores. Due to the lack of such data, it is not possible to compare these results with three previous publications concerning this treatment modality [ 32 , 34 , 35 ]. In the data from the literature on pharmacological treatment, the percentage of patients achieving mucosal healing after the period of induction therapy was several percent for steroids [ 36 ] and ranged from several to nearly 40% for biological treatment, according to the molecule used [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the patients under analysis, a 12-week treatment with CDED + PEN resulted in normalization of fecal calprotectin level in 35%, while 33% achieved such an effect in combination with normal CRP and PCDAI scores. Due to the lack of such data, it is not possible to compare these results with three previous publications concerning this treatment modality [ 32 , 34 , 35 ]. In the data from the literature on pharmacological treatment, the percentage of patients achieving mucosal healing after the period of induction therapy was several percent for steroids [ 36 ] and ranged from several to nearly 40% for biological treatment, according to the molecule used [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the group treated with the CDED + PEN, in contrast to the control group, a reduction in intestinal permeability and the beneficial changes in the composition of microbiota [ 32 ] and in the metabolome [ 33 ] were shown, which may be important in the long-term maintenance of treatment effects. In the last year, the high efficacy of such nutritional therapy has been confirmed in the adult population [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…More recent data from a retrospective study in adults with active Crohn's disease showed that oral polymeric EEN was well tolerated and effective at inducing biochemical and clinical remission [41]. In addition, a recent study found that the Crohn's disease exclusion diet (CDED), which avoids products with a pro-inflammatory effect, resulted in 82.1% clinical remission at 12 weeks and significantly lower calprotectin levels compared with the baseline [42 ▪ ].…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…The authors concluded that CDED is an effective therapy for inducing remission in the adult CD population (78). In another adult CD cohort, Yanai et al performed an open-label, pilot randomised, where eligible patients were biologic naïve adults with mild-to-moderate disease, randomly assigned to CDED plus PEN or CDED alone for 24 weeks.…”
Section: Crohn's Disease Exclusion Diet (Cded)mentioning
confidence: 99%